Activation of the ERK1/2 pathway mediates the neuroprotective effect provided by calycosin treatment. (1st January 2023) - You, Shaohua; Wang, Yanfeng; Guo, Yongxin; Guo, Chao; Cao, Fuyang; Shi, Wenzhu; Yang, Lujia; Mi, Weidong; Tong, Li
Highlights: Calycosin had neuroprotection on neurons injured by oxygen-glucose deprivation reperfusion in vitro. Calycosin exerts neuroprotective effects against ischemia–reperfusion injury in vivo. The ERK signaling pathway participates in the neuroprotective role of calycosin. Abstract: Calycosin is a natural product extracted from some plant families and exhibits various biological properties. But the effect of calycosin on cerebral ischemia–reperfusion injury has not been fully elucidated. In this study, the neuroprotective effect of calycosin treatment on the differentiated SH-SY5Y cells exposed to OGD was evaluated using MTT and flow cytometry. Rats that were pretreatment with calycosin were subjected to MCAO, neurological behavior scores and brain infarct volume were evaluated. The protein expression of pERK/ERK were assessed using Western blot. siRNA-pERK and U0126 were administered to investigate the impact of the ERK pathway on calycosin preconditioning. The results demonstrated the neuronal viability in the calycosin-treated SH-SY5Y cells increased significantly, and the rate of apoptosis decreased compared with the Oxygen-glucose deprivation only SH-SY5Y cells. Calycosin pretreatment reduced infarct volume and improved neurological outcome in rats subjected to MCAO. Administration of calycosin increased the ratio of pERK/ERK expression, which was down-regulated in ischemia–reperfusion group. Down-regulation of pERK/ERK significantly attenuated the neuroprotective effect induced by calycosin pretreatment in vitro and in vivo. We concluded calycosin treatment could induce a neuroprotective effect against ischemia, which was related to the regulation of the ERK1/2 pathway.